The Use of English Native Speaker YouTube Videos in Improving Students’ Speaking Abilities: An Interactive Learning Approach - Wahyudin, Wahyudin (International Journal of English Language and Pedagogy, 2024)
This study investigates the impact of collaborative learning strategy on the reading comprehension of non-English department students at the university level. Using a mixed-method approach, this study combines quantitative data from reading tests with qualitative insights from student interviews and classroom observations. Over one semester, students from various non-English department participated in collaborative activities, such as jigsaw reading and group discussions, designed to improve critical thinking and collaborative problem-solving. The quantitative results demonstrate significant improvements in reading comprehension, particularly in identifying main ideas, making inferences, and understanding vocabulary in context. Qualitative findings reveal that students found the collaborative learning environment enjoyable and motivating, with many reporting that group work reduced their anxiety and enhanced their willingness to participate actively. This study highlights the effectiveness of cooperative learning techniques in improving reading comprehension among non-English department students and offers practical recommendations for integrating these strategies into diverse academic disciplines. Keywords: Collaborative Learning, Reading Comprehension, EFL, Non-English Department